The Implementation of Halal Slaughterhouse in the Perspective of Talcott Parson's Functional Structural Theory - Hikmatul Hasanah; Agung Suwandaru (Journal of Islamic Studies and Civilization, 2023)
Large-scale slaughterhouses and meat producers catering to the broader community as consumers bear the ongoing responsibility of ensuring the sustainability of their businesses. Consequently, continuous structural and functional improvements must be prioritized to foster trust, safety, and comfort within the wider community. The halal abattoir operates as an "action" system, striving to maintain its sustainability by fulfilling the four functions outlined in Talcott Parson's functional structural theory: adaptation, goal attainment, integration, and latency or pattern maintenance. To remain viable and function optimally, the abattoir must execute these four functions effectively. Consumer protection activities are integral, encompassing the public's choices in meat consumption. This involves not only the establishment of halal abattoirs but also the meticulous execution of their functions to meet and exceed the expectations of the community